Aplikasi Akad Ijarah dalam Layanan Pembiayaan Gadai Perspektif Hukum Ekonomi Syariah - Nur Indah Putri Liana (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The background of writing this thesis selection is the situation where the rahn financing at the KSPP Syariah BMT NU Tenggarang branch uses two contracts simultaneously or multiple contracts, namely rahn and ijarah contracts. This study aims to determine the application of ijarah and rahn contracts in syariah pawn services at the KSPP Syariah BMT NU Tenggarang branch and to find out whether the two contracts applied at the KSPP syariah BMT NU Tenggarang branch are in accordance whit the provisions of Islamic Economic Law. The method used in the study is to use a type of field research and a qualitative approach, through data collection by observation. There are two sources of data in this study, namely primary data obtained from the staff of the KSPP Syariah BMT Nu Tenggarang branch and other references related to the research problem under study. Furthermore, the data ware analyzed through the descriptive analysis method, that is, after all the data has been collected, the researcher will explain in detail and systematically so that the final conclusions can be clearly described and understood, also by looking at the review of Syariah Economic Law and referring to the arguments and opinions the experts. The result of the study indicate that the implementation of Syariah pawn financing product services at KSPP Syariah BMT NU Tenggarang branch in determining the cost of deposit services (ijarah) on rahn transactions in practice at the KSPP Syariah BMT NU Tenggarang branch in general is in accordance with the Islamic Ekonomi Of Law.